Synthesis and Crystal Structure of the Electron‐Rich Cyano‐Rhodate Ba3[Rh(CN)3]1. Issue 6 (6th May 2015) - Jach, Franziska; Höhn, Peter; Prots, Yurii; Ruck, Michael
Abstract Brownish gray microcrystalline powders of Ba3[Rh(CN)3] were synthesized from pellets of mixtures of Ba2N, rhodium, NaCN, and graphite at 1070 K in an argon atmosphere. Synchrotron powder diffraction data at 293(1) K revealed the crystal structure of the compound [P63/m, a = 9.23266(7) Å, c = 5.81612(6) Å] is isostructural to Ba3[Co(CN)3] and Ba3[Ir(CN)3]. The trigonal‐planar complex [Rh(CN)3]6– is surrounded by nine Ba2+ cations forming a tri‐capped trigonal prism. Compared to typical cyano ligands, the C–N bond is long [1.21(5) Å] and the vibrational frequencies are low (IR 1674 cm–1, Raman 1728 cm–1).